The Demographic Situation of Hongkong / United Nations. Economic and Social Commission for Asia and the Pacific - United Nations. Economic and Social Commission for Asia and the Pacific (ESCAP, 1974)
165 halaman : ilustrasi, gambar, tabel, diagram ; 27 cm